2021
DOI: 10.1016/j.ajem.2020.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the severity COVID-19 infection on electrocardiography

Abstract: Objective Acute myocardial damage is detected in a significant portion of patients with coronavirus 2019 disease (COVID-19) infection, with a reported prevalence of 7–28%. The aim of this study was to investigate the relationship between electrocardiographic findings and the indicators of the severity of COVID-19 detected on electrocardiography (ECG). Methods A total of 219 patients that were hospitalized due to COVID-19 between April 15 and May 5, 2020 were enrolled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 37 publications
2
51
1
1
Order By: Relevance
“…Similar to our study, a cohort study of 756 patients with COVID-19 found that prior MI pattern, unspeci c repolarization abnormalities and T-wave inversion at hospital admission were associated with death while sinus tachycardia was not [21]. Further, patients with ST-T pathology at hospital admission have a higher risk of developing more severe disease [22]. In one study of 850 patients with ECG recorded at presentation to the emergency department, and another study of 269 patients that analysed ECG at hospital admission and the seventh day of hospitalization found that ST-T-pathology were predictive of death and invasive ventilation [23,33].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar to our study, a cohort study of 756 patients with COVID-19 found that prior MI pattern, unspeci c repolarization abnormalities and T-wave inversion at hospital admission were associated with death while sinus tachycardia was not [21]. Further, patients with ST-T pathology at hospital admission have a higher risk of developing more severe disease [22]. In one study of 850 patients with ECG recorded at presentation to the emergency department, and another study of 269 patients that analysed ECG at hospital admission and the seventh day of hospitalization found that ST-T-pathology were predictive of death and invasive ventilation [23,33].…”
Section: Discussionsupporting
confidence: 85%
“…The electrocardiogram (ECG) is a readily available, non-invasive, radiation free diagnostic mainstay of cardiac pathology [15] used at some point in nearly all severely ill patients [16]. ECG abnormalities in patients with COVID-19 have been described in small case series early during the pandemic [17][18][19][20] and analyses of larger cohorts have found that ECG pathology at hospital admission was associated with more severe disease and higher mortality [9,[21][22][23][24]. Unfortunately, previous studies have not speci cally investigated patients admitted to the intensive care unit (ICU), who have the highest mortality [5].…”
Section: Introductionmentioning
confidence: 99%
“…32 In our study, mean QTc was higher among patients with severe disease and showed significance difference among severe and non-severe patient groups (p=0.005). No such difference was observed in a study by Ali et al 33 The relationship between ST-T changes on ECG and myocardial damage with poor prognosis has been demonstrated. 34 Abnormal ST segment deviation (elevation/depression) and T inversion together, were the most common (27.7%) abnormal ECG manifestation in our study.…”
Section: Discussionmentioning
confidence: 84%
“…In another study, most patients had ECG pathology, including atrial fibrillation / flutter (5.6%), AV block (2.6%), premature atrial contractions (7.7%), premature ventricular contractions (3.4%), left-axis deviation (13.8%), right-axis deviation (5.5%), right-bundle branch block (7.8%), left-bundle branch block (1.5%), left ventricular hypertrophy (15.5%), right ventricular hypertrophy (4%), pathological Q wave (13.9%), localized ST elevation (0.7%), and localized T wave inversion (10.5%) [12]. In a study conducted in our country, tachycardia was found in 31%, ST segment pathology in 28%, T negativity in 22%, ST depression in 20%, and long QT in 5% of the patients [13]. In yet another study, ST-T abnormalities were reported in 30% and left ventricular hypertrophy, in 33% of the patients [14].…”
Section: Discussionmentioning
confidence: 96%
“…Deng Q et al reported that myocarditis, segmental wall motion abnormality on ECG, pulmonary hypertension, and pericardial effusion were more common and the mean ejection fraction was lower in patients with severe disease; however, tachycardia and ST segment pathologies were not different between patients with and without severe disease [15]. McCullugh et al reported that many pathological ECG findings were more common in nonsurviving patients, and in a study conducted in Turkey, ST segment pathologies, ST depression, and T negativity were reported more commonly in patients with severe disease [12,13]. In a COVID-19 case series of 18 patients with ST elevation, this ECG pathology occurred at the time of admission in 10 patients, and the outcome was mortality in 13 patients [16].…”
Section: Discussionmentioning
confidence: 99%